2023
DOI: 10.1002/bco2.212
|View full text |Cite
|
Sign up to set email alerts
|

Genomic alterations in neuroendocrine prostate cancer: A systematic review and meta‐analysis

Abstract: Background: Neuroendocrine prostate cancer (NEPC) is a lethal subtype of prostate cancer. We performed a systematic review and meta-analysis to evaluate the prevalence of genomic alterations in NEPC and better understand its molecular features to potentially inform precision medicine.Methods: EMBASE, PubMed, and Cochrane Central Register of Controlled Trials databases were searched for eligible studies until March 2022. Study qualities were assessed using the Q-genie tool. The prevalence of gene mutations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Loss of function in TP53 or RB1 is not observed in a few t‐NEPC cases 10 . These genomic features may be deeply involved in the development of t‐NEPC; 3 however, we did not observe these gene mutations in our patient, indicating there might be other genomic or epigenetic alterations that trigger t‐NEPC arising from initial adenocarcinoma 11 . t‐NEPCs often present poorer prognosis than common prostate adenocarcinoma 4 .…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Loss of function in TP53 or RB1 is not observed in a few t‐NEPC cases 10 . These genomic features may be deeply involved in the development of t‐NEPC; 3 however, we did not observe these gene mutations in our patient, indicating there might be other genomic or epigenetic alterations that trigger t‐NEPC arising from initial adenocarcinoma 11 . t‐NEPCs often present poorer prognosis than common prostate adenocarcinoma 4 .…”
Section: Discussionmentioning
confidence: 50%
“… 10 These genomic features may be deeply involved in the development of t‐NEPC; 3 however, we did not observe these gene mutations in our patient, indicating there might be other genomic or epigenetic alterations that trigger t‐NEPC arising from initial adenocarcinoma. 11 t‐NEPCs often present poorer prognosis than common prostate adenocarcinoma. 4 Following the National Comprehensive Cancer Network guidelines version 1.2023, the standard treatment for NEPC is chemotherapy with ETP and platinum‐based drugs such as CDDP.…”
Section: Discussionmentioning
confidence: 99%
“…However, it can assess the uptake and accumulation of the non-metabolizable glucose analogue 18 F-FDG, which often correlates with glycolytic flux and lactate synthesis in cancer. 18 F-FDG PET shows a limited usefulness in the detection and staging of primary PCa, whose oxidative/lipogenic phenotype is better captured using precursor radionucleotides such 11 C/ 18 F-choline and 11 C-acetate [17,114]. During castration resistance, PCa undergoes the glycolytic switch and enhances glucose uptake, which can be captured with 18 F-FDG PET.…”
Section: Preclinical/ex-vivo Studiesmentioning
confidence: 99%
“…On this basis, 18 F-FDG PET can be exploited to monitor disease progression and predict the response to ADT before clinical effects are evident. Oyama et al have indeed shown that 18 F-FDG outperforms 11 C-acetate in monitoring ADT efficacy in CWR22 xenograft tumors from mice that were exposed to ADT (diethylstilbestrol) or a vehicle for a week. While 11 C-acetate uptake did not show a significant difference after ADT treatment, 18 F-FDG uptake was already markedly reduced, suggesting that 18 F-FDG PET may predict the ADT response [17].…”
Section: Preclinical/ex-vivo Studiesmentioning
confidence: 99%
See 1 more Smart Citation